Exploring the Evolution of English: From Old English to Modern English - Bakbergenov Aybek (Journal of Higher Education and Academic Advancement, 2024)
This article explores the fascinating evolution of the English language from its origins as Old English to its present form as Modern English. It delves into the historical, social, and cultural factors that have shaped the language at each stage, highlighting significant milestones and influences along the way. The article also discusses the impact of globalization, technology, and regional variations on the development of English, offering insights into its future trajectory.